2003
DOI: 10.1177/1534734603002001006
|View full text |Cite
|
Sign up to set email alerts
|

Plant Medicines of Indian Origin for Wound Healing Activity: A Review

Abstract: Research on wound healing drugs is a developing area in modern biomedical sciences. Scientists who are trying to develop newer drugs from natural resources are looking toward the Ayurveda, the Indian traditional system of medicine. Several drugs of plant, mineral, and animal origin are described in the Ayurveda for their wound healing properties under the term Vranaropaka. Most of these drugs are derived from plant origin. Some of these plants have been screened scientifically for the evaluation of their wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(137 citation statements)
references
References 11 publications
2
126
0
Order By: Relevance
“…Different authors [12][13], have noted that consumption of fruits and vegetables help to prevent diseases such as cancer, ulcers, etc; and as well remedy disease conditions such as gastrointestinal disease, malaria, hepatitis, pile, liver cirrhosis, etc [14][15][16][17][18][19][20]. Studies have shown that these fruits and vegetables are able to play these vital roles due to the presence of chemical constituents found in them, which are bioactive in nature [8][9][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Different authors [12][13], have noted that consumption of fruits and vegetables help to prevent diseases such as cancer, ulcers, etc; and as well remedy disease conditions such as gastrointestinal disease, malaria, hepatitis, pile, liver cirrhosis, etc [14][15][16][17][18][19][20]. Studies have shown that these fruits and vegetables are able to play these vital roles due to the presence of chemical constituents found in them, which are bioactive in nature [8][9][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The wound healing property of F. racemosa is mentioned in different Ayurvedic texts and in a research study the ointment prepared from the powder of the leaves with petroleum jelly (15% w/w) in an 8 mm full-thickness punch wound rat model showed highly significant generation of tissue DNA (1.73 mg/g), RNA (1.17 mg/g), and total protein (16.62 mg/g) during the healing process in comparison with untreated control rats (Biswas & Mukherjee, 2003). Li et al (2004) evaluated the cytotoxic effect of ethanol extracts of F. racemosa bark using ATP-based luminescence assay in human skin fibroblasts (1BR3), human hepatocytes carcinoma (HEPG2) and human promyelocytic leukemia (HL-60) of cell density 1 x 10 4 cells/ mL.…”
Section: Wound Healing Propertymentioning
confidence: 99%
“…The root extract of R. cordifoliawas reported as an effective wound healing principle in experimental models as wound healer 28 . Ethanolic extract and the hydrogel formulation of roots were found to be effective in the functional recovery and healing of wounds and also lead to histo-pathological alterations 29 .…”
Section: Wound Healing Activity:-mentioning
confidence: 99%